Near-infrared upconversion multimodal nanoparticles for targeted radionuclide therapy of breast cancer lymphatic metastases - Zhang, Chuan; Zhang, Yujuan; Liang, Maolin; Shi, Xiumin; Jun, Yan; Fan, Longfei; Yang, Kai; Wang, Feng; Li, Wei; Zhu, Ran (Frontiers in Immunology, 2022)
The theranostics of lymph node metastasis has always been one of the major obstacles to defeating breast cancer and an important decisive factor in the prognosis of patients. Herein, we design NaGdF4:Yb,Tm@NaLuF4 upconversion nanoparticles with PEG and anti-HER2 monoclonal antibody (trastuzumab, Herceptin) (NP-mAb) , the delivery of NP-mAb through the lymphatic system allows for effective targeting and accumulation in lymphatic metastasis. Combination of radionuclides 68Ga and 177Lu could be chelated by the bisphosphate groups of NP-mAb. The obtained nanoprobe (NP-mAb) and nanonuclear drug (68Ga-NP-mAb or 177Lu-NP-mAb) exhibited excellent stability and show high accumulation and prolong retention in the lymph node metastasis after intratumoral injection into the foot pad by near-infrared fluorescence (NIRF), single-photon emission computed tomography (SPECT) and positron emission tomography (PET) imaging. Utilizing the β-rays released by 177Lu, 177Lu-NP-mAb could not only decrease the incidence of lymph node metastasis, but also significantly decrease the volumes of lymph node metastasis. Additionally, 177Lu-NP-mAb induce no obvious toxicity to treated mice through blood routine, liver and kidney function assay. Therefore, nanoprobe and nanonuclear drug we designed could be acted as excellent theranostics agents for lymph node metastasis, providing potential alternatives diagnose and treatment option for lymph node metastasis.